Surgical treatment of slipped capital femoral epiphysis (SCFE) by Dunn procedure modified by Ganz: a systematic review - Giulio Gorgolini; Alessandro Caterini; Kristian Efremov; Lidio Petrungaro; Fernando De Maio; Ernesto Ippolito; Pasquale Farsetti (BMC Musculoskeletal Disorders, 2022)
Abstract Background Treatment of SCFE is still controversial, especially in moderate and severe forms. Dunn osteotomy performed with the Ganz approach became very popular in the last decade, although it is a complicated and challenging surgical procedure with a risk of AVN. The aim of our study was to analyze the current literature verifying the effectiveness of this surgical procedure, with specific attention to the incidence of AVN and other complications. Main body A systematic review on the subject was performed according to the PRISMA guidelines. A literature search was performed by searching all published articles about the topic in the databases. The articles were screened for the presence of the following inclusion criteria: patients affected by slipped capital femoral epiphysis (SCFE) surgically treated by Dunn osteotomy using the Ganz surgical approach. All the patients affected by pathologies other than SCFE, treated without surgery or with procedures not including a surgical hip dislocation were excluded. Based on inclusion and exclusion criteria, 23 studies were included in our systematic review. Selected articles were published from 2009 to 2021 and they included 636 overall hips. According to the selected articles, Dunn osteotomy modified by Ganz, performed by an experienced surgeon, allows for anatomical reduction of moderate or severe SCFE with a low incidence of AVN. Conclusions The few papers with long term follow-up, reported no progression of hip osteoarthritis, however, since the patients are adolescent at surgery, longer follow-up studies are needed to validate this statement. It is still debated if better results are obtained in stable or unstable SCFE. The indication of this procedure in mild SCFE remains controversial. Level of evidence 3